2015
DOI: 10.1016/j.jtcvs.2014.11.081
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid approach to the comprehensive stage II operation in a subset of single-ventricle variants

Abstract: This hybrid comprehensive stage II operation appears feasible and technically simpler than the conventional comprehensive stage II procedure. It is applicable to a subset of single-ventricle cases in which aortic outflow is anticipated to remain unobstructed. We recommend early postoperative anticoagulation to avoid early left pulmonary artery thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Other groups did not find significant differences in systemic ventricular function [45,46] but indicated that impaired systolic right ventricular strain and strain rate values may be indicative of a subclinical functional decline that becomes relevant during follow-up [46]. After aortic arch reconstruction, patients with initial hybrid palliation also showed higher arterial resistance but better Nassar [38] Pulmonary artery stent graft baffle instead of arch reconstruction at comprehensive stage II DeCampli [39] arterioventricular coupling compared with primary Norwood patients [47]. Bilateral pulmonary artery banding shows a similar diastolic pulmonary runoff than that seen with modified Blalock-Taussig shunts [42].…”
Section: Postoperative Hemodynamics and Ventricular Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other groups did not find significant differences in systemic ventricular function [45,46] but indicated that impaired systolic right ventricular strain and strain rate values may be indicative of a subclinical functional decline that becomes relevant during follow-up [46]. After aortic arch reconstruction, patients with initial hybrid palliation also showed higher arterial resistance but better Nassar [38] Pulmonary artery stent graft baffle instead of arch reconstruction at comprehensive stage II DeCampli [39] arterioventricular coupling compared with primary Norwood patients [47]. Bilateral pulmonary artery banding shows a similar diastolic pulmonary runoff than that seen with modified Blalock-Taussig shunts [42].…”
Section: Postoperative Hemodynamics and Ventricular Functionmentioning
confidence: 99%
“…DeCampli and colleagues [39] modified the comprehensive stage II procedure by creation of a stented baffle within the pulmonary artery. The baffle connected both pulmonary artery branches while isolating them from the main pulmonary artery-to-aorta pathway, thereby keeping the native main pulmonary artery, aortic, and ductal anatomy.…”
Section: Other Hybrid Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite important improvements in surgical outcomes, management of patients with single-ventricle physiology and systemic outflow obstruction remains difficult, and renewed efforts are aimed at achieving improved functional outcomes. The work presented by DeCampli and colleagues 1 in this issue of the Journal represents a new approach to simplify the intervention commonly undertaken as the second-stage palliation in those patients who have previously undergone a hybrid procedure for single-ventricle physiology. As stated by DeCampli and colleagues, 1 ''a substantial decrease in trauma at the second stage could tip the balance in favor of the hybrid approach.''…”
mentioning
confidence: 99%
“…As we know 3 decades later, these created a setup for multiple and recurrent interventions, associated with scarring, fibrosis, and unintended effects, which complicated further surgery and intervention. 4 Finally, as DeCampli and colleagues 1 have clearly pointed out, the presence of sufficient antegrade blood flow to perfuse the brachiocephalic vessels is essential, limiting the applicability of this approach among patients with single-ventricle physiology and systemic outflow obstruction.…”
mentioning
confidence: 99%